2015
DOI: 10.1039/c4tx00064a
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic cyanide toxicity on male reproductive system of albino rat

Abstract: Sexually mature albino rats were orally treated with sodium cyanide, NaCN (0, 0.64, 1.2 and 3.2 mg kg −1 BW) for 90 days. After 90 days of treatment, the rats were euthanized and male reproductive functions were assessed by histopathology, sperm head counts, sperm motility, sperm morphology and hormonal assay. Only a higher dose (3.2 mg kg −1 BW) of NaCN caused significant changes in body and reproductive organs weight, sperm motility, sperm count, sperm abnormality and in the levels of luteinizing hormone (LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The current study was undertaken to investigate the oxidative damage in rat sperms induced by subchronic cyanide intoxication. The results obtained from body weight gain, reproductive organ weight, hormone levels, sperm count, sperm motility and sperm abnormality were in line with our previous work [60] . Further, in our previous work we have also revealed that, higher doses of cyanide can induce changes in histoarchitecture of testis, epididymis and prostate and it has been presumed due to the induced oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…The current study was undertaken to investigate the oxidative damage in rat sperms induced by subchronic cyanide intoxication. The results obtained from body weight gain, reproductive organ weight, hormone levels, sperm count, sperm motility and sperm abnormality were in line with our previous work [60] . Further, in our previous work we have also revealed that, higher doses of cyanide can induce changes in histoarchitecture of testis, epididymis and prostate and it has been presumed due to the induced oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Shivanoor and David (2015) observed no changes in body weight and reproductive organs weight of rats perorally treated with sodium cyanide (doses 0.64 and 1.2 mg/kg) for 90 days. Similarly, Shivanoor and David (2015) observed no changes in body weight and reproductive organs weight of rats perorally treated with sodium cyanide (doses 0.64 and 1.2 mg/kg) for 90 days.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, no significant effect of long-term consumption of apricot seeds on total body weight, femoral weight and length was demonstrated. Similarly, Shivanoor and David (2015) observed no changes in body weight and reproductive organs weight of rats perorally treated with sodium cyanide (doses 0.64 and 1.2 mg/kg) for 90 days. It was also determined that peroral application of potassium cyanide did not influence goats' body weight after 90 days (Soto-Blanco & Górniak, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…In a more recent rat study (Shivanoor and David, ), effects on the male reproductive system were also reported mainly in the high‐dose group, i.e. decreased absolute testis, epididymis and prostate weights; decreased sperm count and motility, sperm abnormality; changes in hormone levels (FSH, LH, testosterone); and histopathological changes in testis, epididymis and prostate.…”
Section: Assessmentmentioning
confidence: 91%
“…For five (Jackson, ; NTP, ; Sousa et al., ; Manzano et al., ; Shivanoor and David, ) of 15 studies, dose descriptors (i.e. NOAEL, Lowest observed adverse effect level (LOAEL) or BMDL) were available (Table ).…”
Section: Assessmentmentioning
confidence: 99%